Evaluating the influence of financial investment in compulsory education on the health of Chinese adolescents: a novel approach - Kewen Yang; Shah Fahad; Feimin Yuan (BMC, 2022)
Abstract Background With China's aging and declining fertility rate, the importance of population quality is increasing. As the main force of the labor market in the future, the Chinese government tries to promote the development of adolescents by increasing the financial investment in compulsory education, so as to improve the future population quality of China and enhance the national competitiveness. Therefore, the aim of this study was to investigate the relationship between financial investment in compulsory education and the health of Chinese adolescents. Methods This study specifically uses data obtained from China Education Panel Survey (CEPS). The data were nationally representative, which covered families, schools, and communities. For the CEPS data obtained, the 2013-2014 school year was the baseline, and two cohorts of 7th and 9th graders were the starting point of the survey. In the 2014-2015 school year, 8th-grade students who participated in the baseline survey (7th-grade students in the 2013-2014 school year) were followed up. Since the second period only began to investigate the data on financial investment in compulsory education, this article uses the data from the 2014-2015 academic year for research. OLS and Ordered Probit models were used to investigate the impact of financial investment in compulsory education on adolescent health. Results With the doubling of financial investment in compulsory education, self-rated health increased by 0.021, frequency of illness decreased by 0.03, the number of sick leave days decreased by 0.207, and depression decreased by 0.191. The heterogeneity analysis shows that compared to only-child, high-income and nonagricultural groups, the financial investment in compulsory education has a greater impact on the health of adolescents with the characteristics of agriculture hukou, non-only-child and low-income families. Further analysis of the impact mechanism shows that financial investment in compulsory education exerts a significant influence on the health of adolescents by easing family budget constraints, improving school sports facilities, and increasing the expected return of health investment and social capital. Conclusions Financial investment in compulsory education can enhance the health of adolescents, and vulnerable groups benefit more, which is conducive to promoting health equity.